Service Quality and Customer Loyalty in the Online Food Delivery Service Industry - Made Elsiana; Agus Fredy Maradona (Quantitative Economics and Management Studies, 2024)
There has been a significant increase in revenue in the online food delivery sector, reaching 43.2%, as a result of the COVID-19 pandemic in Indonesia. Prior to the pandemic, consumers would occasionally order food for delivery, but now it has become a regular practice. Currently, GoFood, GrabFood, and ShopeeFood dominate the food delivery market in Indonesia. This trend presents both opportunities and challenges for businesses, as it creates a more competitive ecosystem. Therefore, it is crucial for online businesses to cultivate loyal customers in this environment. This study aims to investigate the extent of customer loyalty to online food delivery services and explore the possible mediating effects of customer satisfaction and corporate image. The research population is an unknown number of consumers of GoFood, GrabFood and ShopeeFood in Denpasar - Bali. The technique of determining the sample using purposive sampling, the number of respondents as many as 122 people. The research instrument used a questionnaire, which was analyzed by SmartPLS. This study found that service quality does affect customer loyalty, but the effect is not statistically significant. In contrast, research shows that customer satisfaction and corporate image are significant mediators in the relationship between service quality and customer loyalty. The implication for service providers is to focus on increasing customer satisfaction and maintaining a positive corporate image to increase customer loyalty. This can be achieved through regular evaluation and service innovation, which can lead to a successful business.